Planejamento educacional e participação democrática: um estudo sobre a rede pública estadual de ensino em Alagoas (1999-2004) - Cruz Neto, Tiago Leandro da (2008)
This study aimed at investigating the educational planning from 1999 to 2004 under the perspective of the school participation accomplished by the State bureaucratic apparatus, the Executive Secretary of Education of the State of Alagoas (SEE/AL), in the north-east of Brazil, since the setting up of the democratic education management model in the system in1999. This research was a case study where the qualitative approach was considered under the dialectical social-historical conception, using qualitative techniques: documentary primary and secondary documents, questionnaires and semi-structured interviews with the technicians from the Executive Secretary of Education members of the school community - students, teachers, staff and parents. The accomplished study reveals that, during the setting up period of the democratic educational management in 1999, the restricted State of Alagoas, tried to get to know the community s demands so as to plan some actions intended to fulfill a participation culture through mechanisms established throughout the whole public system where there weren t any previously. However, it is inferred that most of the times the planned actions became exhausted as institutionalization and orientation for the teaching units, of a political and pedagogical content, being much more restricted to bureaucratic guidance of the working of the established mechanisms, such as filling in reports, receipts, and so on. Therefore, it was planned a few actions which promoted a more committed basis participation from segments such as the parents and students , through school societies and parents associations in the schools, thus weakening the democratic quality. The planning process itself inserted within a little participative environment with traditional type characteristics within the SEE s bureaucratic apparatus, the lack of a accomplishing a shared planning, and the constant changing of SEE managers resulted in consequences in the planned actions. Therein, the SEEL s discourse of building up a citizen school collided with the limitation of the State bureaucratic apparatus which has circumscribed itself to the planning of a relative participative culture, planning which widened participation to a determined extent, but intended a few learning actions of an active kind of participation.